2003
DOI: 10.1073/pnas.1834432100
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative, highly sensitive cell-based infectivity assay for mouse scrapie prions

Abstract: Prions are usually quantified by bioassays based on intracerebral inoculation of mice that are slow, imprecise, and costly. We have isolated neuroblastoma N2a sublines highly susceptible to mouse prions, as evidenced by accumulation of infectivity and the scrapie form of prion protein (PrP Sc ), and developed quantitative in vitro assays for prion infectivity. In the scrapie cell (SC) assay, susceptible N2a cells are exposed to prion-containing samples for 3 days, grown to confluence, and split 1:10 three time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
433
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(447 citation statements)
references
References 25 publications
(33 reference statements)
13
433
1
Order By: Relevance
“…They fall into three categories: Western blots, enzyme-linked immunosorbent assays (ELISAs), and the conformation dependent immunoassay (CDI). The most widely used test is the Western blot, which is reported to detect between 10 to 20 pmol ofÅ PrP ScÅ [16Å -18].Å ELISAÅ methodologyÅ isÅ moreÅ sensitive, andÅcanÅdetectÅ2ÅpmolÅofÅPrP ScÅ [19Å -21].ÅTheÅCDI immunoassay is the most sensitive method reported, capable of detection of 0.1 pmol of PrP Sc in brain homogenateÅ (2Å ngÅ ofÅ PrPÅ ofÅ MWÅ 16,241)Å [22].Å Methods to amplify prion titer before detection using either cell cultureÅ [23]Å orÅ cell-freeÅ conversionÅ assaysÅ [24,Å 25]Å show considerable promise. Despite the advancements made in analytical methodology for prion analysis, apparently the detection limit needs to be improved by about three orders of magnitude to allow detection of prions in blood (vide supra, 30 amol/mL in blood versus 0.1 pmol detection by the best antibody methods).…”
mentioning
confidence: 99%
“…They fall into three categories: Western blots, enzyme-linked immunosorbent assays (ELISAs), and the conformation dependent immunoassay (CDI). The most widely used test is the Western blot, which is reported to detect between 10 to 20 pmol ofÅ PrP ScÅ [16Å -18].Å ELISAÅ methodologyÅ isÅ moreÅ sensitive, andÅcanÅdetectÅ2ÅpmolÅofÅPrP ScÅ [19Å -21].ÅTheÅCDI immunoassay is the most sensitive method reported, capable of detection of 0.1 pmol of PrP Sc in brain homogenateÅ (2Å ngÅ ofÅ PrPÅ ofÅ MWÅ 16,241)Å [22].Å Methods to amplify prion titer before detection using either cell cultureÅ [23]Å orÅ cell-freeÅ conversionÅ assaysÅ [24,Å 25]Å show considerable promise. Despite the advancements made in analytical methodology for prion analysis, apparently the detection limit needs to be improved by about three orders of magnitude to allow detection of prions in blood (vide supra, 30 amol/mL in blood versus 0.1 pmol detection by the best antibody methods).…”
mentioning
confidence: 99%
“…However, there is also evidence that prion multiplication show cell tropism ex vivo. This is best illustrated for the ME7 strain which does not replicate in N2a or GT1 cell lines [16,67] but does replicate in SN56 [7], L929 [147], and MG20 [61] cell lines.…”
Section: Fibroblast-likementioning
confidence: 99%
“…Following the observation that only a small percentage of cells are actually infected in a typical N2a culture population [115], N2a subclones with much higher permissiveness were isolated [16,41]. These N2a sublines, along with improved detection of PrP res , allowed the development of a quantitative, highly sensitive cell-based infectivity assay for the RML murine prion strain [67]. In the scrapie cell assay (SCA), N2a cells are exposed for a few days to the infectious inoculum, split three times at a 1:10 dilution, then spotted onto filters.…”
Section: Cell Models As Sensitive Bioassay For Prion Infectivitymentioning
confidence: 99%
“…[7][8][9] Some recent approaches for ante mortem diagnosis include applying newly developed ligands against PrP sc , 10,11 conformational-dependent immunoassays, 12,13 spectroscopic techniques, 14,15 and PrP sc amplification. 16,17 Efforts to avoid protease digestion and use of other means to differentiate PrP sc and PrP c are the most desirable, but these methods are under trial and no practical application has been suggested so far. Fischer et al reported the use of plasminogen as a ligand that interacts specifically with PrP sc and not with PrP c .…”
mentioning
confidence: 99%